사시수술중 발생하는 안구심반사 - 조재서; Jae Seo Cho; 김동섭; Dong Seob Kim; 신정철; Jung Chul Shin (Daihan angwa haghoi jabji, 1998)
사시 수술시 발생할 수 있는 안구심반사의 빈도와 외안근에 따른 빈도차를 알아보고자 본 연구를 시행하였다. 1997년 2월부터 1998년 3월까지 전신마취하에 사시수술을 받은 65명의 환자의 123개의 외안근을 대상으로하여 안구심반사를 관찰하였다. 심한 안구심반사를 보이는 11명의 환자에서는 리도케인 구후주사나 아트로핀 정주로 안구심반사를 예방할 수 있는지 관찰하였다. 65명의 환자 중에 43명(66.2%)에서 안구심반사가 일어났고 수술 중 처치를 하지 않은 54명에서 101개의 외안근 중에 47개(46.5%)에서 안구심반사가 나타났다. 양안의 차이는 우안(n=51)은 47.1%, 좌안(n=50)은 46%로 유의한 차이가 없었고(P>0.999) 외안근별로는 내직근과 나머지 외안근간의 유의한 차이는 없었다(P=0.664). 술전 전처치로아트로핀 근주를 시행한 군(n=25)에서는 안구심반사가 유의하게 감소하였다(P=0.018). 안구심반사가 심하게 나타난 11명에서 아트로핀 정주(n=4)나 리도케인 구후주사(n=7)후 안구심반사의 빈도가 27.3%로 감소하였다(P=0.34)(한안지 39:3078-3082, 1998) We perfomed this study to evaluate the incidence of the oculocardiac reflex(OCR) and its difference relative to each extraocular muscles. In addition, preventive methods for oculocardiac reflex were also evaluated. From Febrary 1997 to January 1998, we examined the occurrence of the OCR of 65 patients who underwent strabismus surgery in 123 extraocular muscles under the general anesthesia. Those who showed severe OCR were prepared with retrobulbar injection of 1% lidocaine 2cc or 1% intravenous atropine and observed wheather OCR was prevented. The overall incidence of the OCR was 66.2% and there was no significant difference between the incidence in both eyes(p>0.999). The incidence in each of the extraocular muscles did not show statistically significance when the patients were prepared with preoperative intramuscular atropine(p=0.018). The incidence after intraoperative retrobulbar injection or intravenous atropine was decreased to 27.3% but was not statistically significant(p=0.34)(J Korean Ophthalmol Soc 39:3079-3082, 1998)